TERAPI RELAKSASI OTOT PROGRESIF PADA KLIEN ANSIETAS - Zaini, Mad (Universitas Muhammadiyah Jember, 2017)
Someone who experience physical health problems can cause mental health problem, example anxiety. The purpose of study to illustrate the application of progressive muscle relaxation therapy in anxiety clients. The method used is the case analisys in anxiety clients. The amount of clients are 34 people, 23 clients given ners intervention and progressive muscle relaxation therapy. The results were found decrease the signs and symptoms anxiety. Progressive muscle relaxation therapy is recommended a nursing therapy in anxiety. Keywords : Anxiety, progressive muscle relaxation therapy.